PRIMARY ALVEOLAR PROTEINOSIS - Khan, Abdul Rab; Sulaman, Aamir; Abbasi, Munir Ahmad; Jehanzeb, Muhammad (Journal of Ayub Medical College Abbottabad, 2012)
A 35 years old man presented with primary pulmonary alveolar proteinosis who was admitted to chest unit of ATH through casualty department. Before he came to our ward he was treated with different antibiotics including anti-tuberculosis drugs for a month at least. But his symptoms did not improve rather his dyspnoea got worse. He was misdiagnosed till histopathology revealed that he has pulmonary alveolar proteinosis. With this background we briefly review clinical features, diagnosis and treatment of this rare disease. Keywords: Pulmonary alveolar proteinosis, Dyspnoea, anti-tuberculosis drugs